Expert Consensus Guidelines on Minimally Invasive Donor Hepatectomy for Living Donor Liver Transplantation From Innovation to Implementation: A Joint Initiative From the International Laparoscopic Liver Society (ILLS) and the Asian-Pacific Hepato-Pancreato-Biliary Association (A-PHPBA). Issue 1 (January 2021) - Cherqui, Daniel; Ciria, Ruben; Kwon, Choon Hyuck David; Kim, Ki-Hun; Broering, Dieter; Wakabayashi, Go; Samstein, Benjamin; Troisi, Roberto I.; Han, Ho Seong; Rotellar, Fernando; Soubrane, Olivier; Briceño, Javier; et al.
Abstract : Objective: The Expert Consensus Guidelines initiative on MIDH for LDLT was organized with the goal of safe implementation and development of these complex techniques with donor safety as the main priority. Background: Following the development of minimally invasive liver surgery, techniques of MIDH were developed with the aim of reducing the short- and long-term consequences of the procedure on liver donors. These techniques, although increasingly performed, lack clinical guidelines. Methods: A group of 12 international MIDH experts, 1 research coordinator, and 8 junior faculty was assembled. Comprehensive literature search was made and studies classified using the SIGN method. Based on literature review and experts opinions, tentative recommendations were made by experts subgroups and submitted to the whole experts group using on-line Delphi Rounds with the goal of obtaining >90% Consensus. Pre-conference meeting formulated final recommendations that were presented during the plenary conference held in Seoul on September 7, 2019 in front of a Validation Committee composed of LDLT experts not practicing MIDH and an international audience. Results: Eighteen Clinical Questions were addressed resulting in 44 recommendations. All recommendations reached at least a 90% consensus among experts and were afterward endorsed by the validation committee. Conclusions: The Expert Consensus on MIDH has produced a set of clinical guidelines based on available evidence and clinical expertise. These guidelines are presented for a safe implementation and development of MIDH in LDLT Centers with the goal of optimizing donor safety, donor care, and recipient outcomes.